تأثير المستخلص المائي لألجزاء الخضرية لنبات البربين oleracea Portulaca في بعض الخطوط الخلوية السرطانية والطبيعية - سلمان اسراء صكر; حسن انتصار عبد لله; جاسم نور نعيم (Al-Nahrain Journal of Science, 2018)
The cytotoxic effect of the aqueous extract of Potulaca oleraceae L. was tested in vitro against the cancer cell line Hela (cervical carcinoma), cancer cell line Hep-2 (larynex carcinoma), cancer cell line AMN-3 (Murine mammary) and the normal cell line MEF (Mouse Embryo Fibroblast) at concentrations 100, 200, 400, 600, 800 µg/ ml. The results showed the existence of significant differences in the use of concentrations of low-lying (400 200 100) micrograms / ml of cancer cells Hela and AMN-3 while not giving high concentrations of any obvious effect on the cells. On the contrary, in-line cell cancerous Hep-2 were high concentrations (600, 800) micrograms / ml have a toxic effect and a clear comparison with low-lying concentrations during the exposure periods (24 and 48) hours. While the extract showed no significant effect during the period time of exposure as compared with contact against MEF cells.